Analysis of the Implementation of Video-Based Learning Media on Student Learning Outcomes in the Grade X History Subject at SMA Labschool - Mikhael Oktavian Betalino (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study reviews the results of quantitative experimental research conducted by Mikhael Oktavian Betalino (History Education Study Program, Tadulako University, 2026) regarding the influence of video-based learning media on the understanding levels of Grade X students at SMA Labschool in the subject of History, specifically concerning the topic of the arrival of Islam in Indonesia. The study employed a pretest-posttest control group design involving two classes selected via purposive sampling: one class was taught using video media (experimental group), while the other was taught using conventional methods (control group). Data analysis using SPSS revealed that the experimental group's mean posttest score (77.31) was higher than that of the control group (65.77); a two-tailed t-test yielded a significance value of 0.001 (p < 0.05), indicating the rejection of the null hypothesis and the acceptance of the alternative hypothesis. However, the N-Gain test showed that the magnitude of the improvement in student understanding remained low, at 20.11%. These findings indicate that video-based audiovisual media had a statistically significant effect on student understanding; however, the impact was not yet optimal, suggesting a need for better content planning, longer study duration, and larger sample sizes in future research. This article presents a narrative review of these findings and discusses their practical implications for teachers and schools.